Pulse shape tuning for 1064 nm nanosecond MOPA fibre laser - Liu, Meng (2018)
For a high power 1064 nm nanosecond MOPA pulse fibre laser, the seeding pulse shape is distorted after amplified by pre-amplifier and power-amplifier stages under the effect of gain saturation. As the pulse shape is crucial for some industrial applications, the distortion of eight different shapes of seeding pulses is experimentally studied, and the Stimulated Raman Scattering (SRS) for several shapes is also investigated.